Концептуальна метафора як механізм реалізації когнітивної матриці «Свій–Чужий» у політичному дискурсі (на прикладі виступів А. Меркель) - Семотюк, Орест Любомирович; Semotiuk, O. L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено механізм реалізації когнітивної матриці «свій–чужий» у політичному дискурсі. Показано, що оптимальною для такої реалізації є концептуальна метафора, яка посилює прагматичний вплив на аудиторію. В основі дослідження лежить типологія концептуальних метафор Дж. Лакоффа і М. Джонсона. Доведено, що використання концептуальної метафори уможливлює таку конфігурацію ядерних і периферійних концептів матриці, яка вказує на належність/неналежність політика у вигідному для нього світлі. Проаналізовано основні засоби вербалізації концепту «POLITIK». The article examines the implementation mechanism of cognitive matrix «self-other» in the political discourse. It is shown that the best way for this implementation is the conceptual metaphor, which enhances the pragmatic impact on the audience. The essence of using conceptual metaphor in the political discourse lies in the substitution of matrix «self-other» peripheral concepts through other concepts that are more understandable to the average native speaker. In this article the typology of conceptual metaphors by G. Lakoff and M. Johnson is used. It is shown that the use of conceptual metaphor makes such configuration of nuclear and peripheral matrix concepts that indicates affiliation / non affiliation of the politician in a favorable way for him. The analysis of research material shows that in her speeches Angela Merkel uses ontological, organizational and orientational metaphors and their varieties: anthropomorphic (source domain: «physiology», «relationship»), artifact (source domain: «building», «cities», «mechanism», «household items») and nature (source: «animal», «plant») metaphors. The main means of verbalization of the concept «POLITIK» were analyzed.
Conceptual metaphor as a mechanism of cognitive matrix “Self-other” in the political discourse (based on speeches of A. Merkel)
Keywords: концептуальна метафора; conceptual metaphor; когнітивна матриця; cognitive matrix; політичний дискурс; political discourse